Canaries reflect on the mine : dropouts' stories of schooling - Cameron, Jeanne (Research for social justice., 2012)
In Canaries Reflect on the Mine: Dropouts' Stories of Schooling, Jeanne Cameron invites the reader to see schooling and early school leaving through the eyes of high school dropouts themselves. The transcendent desires revealed by this research - to be known and valued, to learn with purpose and autonomy - are spoken with poignant clarity by the young people who story these pages. This study offers a compelling and timely critique of the dominant, neoliberal discourse on schooling and early school leaving. It challenges conventional wisdom about dropouts, and shows how the experiences and needs of those who leave school early and those who persist to graduation are more similar than different. Collectively, these young people's stories evoke a canary-in-the-mine metaphor, one where the canaries exit and the miners remain. They implore us to see the dropout crisis as a symptom of the alienating and dehumanizing school practices advanced by No Child Left Behind and Race to the Top. More importantly, they offer a vision for schooling that lovingly embraces and extends all students' experiences, enriches their biographies, and celebrates and supports each of their talents and purposes with equal passion. Pre-service and in-service teachers, educational researchers and policy makers, administrators, and advocates for equitable and democratic schooling have much to learn from this book. Qualitative researchers will find a powerful model for working collaboratively with youth to represent their experiences and to craft solutions to the challenges they face. Students of sociology will discover a compelling illustration of C. Wright Mills' sociological imagination and his charge to 'take it big' by drawing connections between individual biographies and the social and historical structures that frame lived experience. For professional social scientists, it embodies Mills' challenge to embrace the moral sensibilities required to understand and improve the human condition.